Contaceptive use spacing after childbirth with contraception failure: IDHS 2012 analysis - Chamy Rahmatiqa; Shinta Prawitasari; Siswanto Agus Wilopo (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Contraceptive use after childbirth and contraception failure: an analysis of Indonesia Demographic Health Survey 2012PurposeThis research aimed to evaluate the use of contraception after childbirth with contraception failure. MethodsThis research was an observational study using IDHS 2012 with a retrospective cohort design. Married women who got pregnant while using contraceptives were the unit of analysis. Statistical analysis used survival analysis with stratified Cox Regression methods.ResultsAnalysis showed a higher failure rate in the traditional contraceptive methods such as coitus interruptus and periodic abstinence. The failure rate of the contraceptive method implant in Indonesia was higher by 10 times the global failure rate. Women who had used contraceptive for 33-48 weeks and >48 weeks after childbirth had higher risk of pregnancy with contraceptive failure (respectively HR=1.25; 95% CI: 0.63-2.47 and 1.91; 95% CI: 1-3.67), respectively. Other factors influencing the contraceptive failure were age and met or unmet needs.ConclusionContraceptive use after childbirth is associated with contraceptive failure among woman of childbearing age in Indonesia. Providers of contraceptive implants may introduce additional variations of implantable contraceptives in Indonesia and are supported by qualified health personnel.